CRISPR gene editing to improve crop resistance to parasitic plants - Jhu, Min-Yao; Ellison, Evan E.; Sinha, Neelima R. (Frontiers in Genome Editing, 2023)
Parasitic plants pose a significant threat to global agriculture, causing substantial crop losses and hampering food security. In recent years, CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) gene-editing technology has emerged as a promising tool for developing resistance against various plant pathogens. Its application in combating parasitic plants, however, remains largely unexplored. This review aims to summarise current knowledge and research gaps in utilising CRISPR to develop resistance against parasitic plants. First, we outline recent improvements in CRISPR gene editing tools, and what has been used to combat various plant pathogens. To realise the immense potential of CRISPR, a greater understanding of the genetic basis underlying parasitic plant-host interactions is critical to identify suitable target genes for modification. Therefore, we discuss the intricate interactions between parasitic plants and their hosts, highlighting essential genes and molecular mechanisms involved in defence response and multilayer resistance. These include host resistance responses directly repressing parasitic plant germination or growth and indirectly influencing parasitic plant development via manipulating environmental factors. Finally, we evaluate CRISPR-mediated effectiveness and long-term implications for host resistance and crop improvement, including inducible resistance response and tissue-specific activity. In conclusion, this review highlights the challenges and opportunities CRISPR technology provides to combat parasitic plants and provides insights for future research directions to safeguard global agricultural productivity.